Model Pembelajaran Berbasis Masalah (Problem Based Learning) Untuk Meningkatkan Kemampuan Berpikir Kritis dan Keterampilan Mengarang Bahasa Arab (Insya) Siswa Kelas VIII di MTs Mardhatillah Al Mumtazah Picung Pandeglang - Iffah Lathifah (Metakognisi, 2020)
The research was aimed to analyze the implementation of problem-based learning in improving critical thinking and the competence standard of writing in Arabian (Insya). The subjects of this study were students in grade VIII at Mardhatillah Al Mumtazah Picung Pandeglang. It included of 36 students. The study used classroom action research, implemented in 3 cycles which included of pra cycle. The activities in any research included planning, implementation, observation and reflection activities. The implementation of this classroom action research used problem-based learning model. This study used 2 (two) kind of instruments in each cycle, they are; student discussion sheet and individual writing test in each last cycle and the observation sheet to analyze the critical thinking ability in data collection. The results showed that the application of problem-based learning model can improve the students’ critical thinking ability and Arabic writing skills (Insya) of grade VIII students at MTs.Mardhatillah Al Mumtazah Picung Pandeglang on Arabic competence Standard. Based on the tests which is conducted in 2 (two) cycles, the result was there is a positive relationship between the value of critical thinking skills with the value of students, Arabic writing skills. If students think critically, it will increase students’ Arabic writing skills more than students’ who has lower critical thinking. It means there is significant influence between the value of students' critical thinking skills with the value of students Arabic writing skills. If the students’ think critically, the students’ could increase their Arabic writing skills.It means there was a significant influence between the value of students' critical thinking skills with the value of student Arabic writing skills.